Factors Affecting the Quality of Life of Patients with Chronic Renal Failure Undergoing Hemodialysis at RSUD Sekarwangi Sukabumi District - Budhiana, Johan; Melinda, Fera; Dewi, Rosliana; Yulianti, Maria; Arsyi, Dila Nurul (STIKep PPNI Jawa Barat, 2024)
Aims: Chronic renal failure is an increasingly prevalent global health issue, with hemodialysis as the most common treatment method. Factors affecting patients' quality of life include age, gender, education, occupation, and treatment duration. This study aimed to identify and examine these factors. Methods: This cross-sectional study involved 80 hemodialysis patients at RSUD Sekarwangi Kabupaten Sukabumi, using total sampling and questionnaires for data collection. Logistic regression was used for data analysis, and the study received ethical approval. Results: The Chi-square test results indicate that age, gender, education, occupation, duration of chronic kidney failure, and length of hemodialysis significantly influence the quality of life in chronic kidney failure patients (p < 0.005). Logistic regression analysis identified education as the dominant factor impacting quality of life (OR = 39.316). Conclusion: The study reveals that age, gender, education, occupation, duration of chronic renal failure, and length of hemodialysis treatment significantly impact the quality of life of patients with chronic renal failure.